Cyber Terrorism and its Prevention in Indonesia - Setiawan, Dian Alan (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
Cyber technology gives birth to criminal activities carried out inside the cyberspace which is technically referred to as cybercrimes. Cybercrime appears in various forms including the so-called cyberterrorism.Â The purpose of this research is to discuss the development of cyberterrorism and to explore the efforts made by the Government in controlling cyberterrorism in Indonesia. This normative legal research examines the application of the relevant legislation, especially Law No. 19 of 2016 regarding the Amendment to Law No. 11 of 2008 on Information and Electronic Transaction and Law No. 5 Year 2018 regarding the Amendment of the Law No. 15 of 2003 on the Eradication of Crime of Terrorism. It is found that the development of cyberterrorism can be prevented through both technological and legal approach.